Jujuboside B Reduces Vascular Tension by Increasing Ca2+ Influx and Activating Endothelial Nitric Oxide Synthase. - Yixiu Zhao; Xin Zhang; Jiannan Li; Yu Bian; Miaomiao Sheng; Bin Liu; Zidong Fu; Yan Zhang; Baofeng Yang (PLoS ONE, 2016)
Jujuboside B has been reported to have protective effect on many cardiovascular diseases. However, the effects of Jujuboside B on vascular tension and endothelial function are unknown. The present study investigated the effects of Jujuboside B on reducing vascular tension, protecting endothelial function and the potential mechanisms. The tension of isolated rat thoracic aorta ring was measured by Wire myograph system. The concentration of nitric oxide (NO) and the activity of endothelial nitric oxide synthase (eNOS) in human aortic endothelial cells (HAECs) were determined by Griess reagent method and enzyme-linked immune sorbent assay. The protein levels of eNOS and p-eNOS at Serine-1177 were determined by western blot analysis. Intracellular Ca2+ concentration in HAECs was measured by laser confocal imaging microscopy. Results showed that Jujuboside B reduced the tension of rat thoracic aorta rings with intact endothelium in a dose-dependent manner. L-NAME, KN93, EGTA, SKF96365, iberiotoxin and glibenclamide significantly attenuated Jujuboside B-induced vasodilation in endothelium-intact tissues. In contrast, indometacin and 4-DAMP had no such effects. Jujuboside B also promoted NO generation and increased eNOS activity, which were attenuated by L-NAME, EGTA and SKF96365. Moreover, Jujuboside B increased intracellular Ca2+ concentration dose-dependently, which was inhibited by EGTA and SKF96365. Besides, Jujuboside B induced a rapid Ca2+ influx instantaneously after depleting intracellular Ca2+ store, which was significantly inhibited by SKF96365. In conclusion, this study preliminarily confirmed that Jujuboside B reduced vascular tension endothelium-dependently. The underlying mechanisms involved that Jujuboside B increased extracellular Ca2+ influx through endothelial transient receptor potential cation (TRPC) channels, phosphorylated eNOS and promoted NO generation in vascular endothelial cells. In addition, Jujuboside B-induced vasodilation involved endothelium-dependent hyperpolarizaiton through endothelial potassium channels. Jujuboside B is a natural compound with new pharmacological effects on improving endothelial dysfunction and treating vascular diseases.